2020
DOI: 10.1186/s12889-020-08658-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with injuries among preschool children in Egypt: demographic and health survey results, 2014

Abstract: Background Childhood injuries are a significant and growing global public health problem, often with high morbidity and, at times, mortality. A large proportion of injuries in preschool children occur in or around the home. We aimed to identify socioeconomic and demographic factors associated with preschool children injuries in Egypt. Methods Secondary data analysis were done for the Egyptian Demographic and Health Surveys (EDHS), 2014. Potential associated factors were measured from data on child welfare and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…Working of the mother had strong effects on childhood injuries. In the current study, children with working mothers had lesser incidence of injuries than housewife mothers, and these results are in accordance with an Egyptian study conducted by Mohammed et al, (2020). In contrary, in a study conducted by (Halawa et al, 2015), the authors showed that children injuries of working mothers had greater incidence than non-working mothers, and they explained that by less time and care of the working mothers for their children (Nathens et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Working of the mother had strong effects on childhood injuries. In the current study, children with working mothers had lesser incidence of injuries than housewife mothers, and these results are in accordance with an Egyptian study conducted by Mohammed et al, (2020). In contrary, in a study conducted by (Halawa et al, 2015), the authors showed that children injuries of working mothers had greater incidence than non-working mothers, and they explained that by less time and care of the working mothers for their children (Nathens et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study the commonest type of injury was contused wound (54 cases) followed by cut wounds (27 cases), fractures (26 cases), crushed wounds (20 cases) and finally burns (12 cases). This was in harmony with (Halawa et al, 2015& Mohammed et al, (2020. In another study conducted by El-Sayed et al, 2002 in Ismailia -Egypt, as the authors reported that the commonest injury was fracture followed by cut wound.…”
Section: Discussionmentioning
confidence: 66%
“…In the same vein, a study conducted by Mohammed et al (10) in Egypt, indicated that the most common reported accidents were an open wound followed by fractures and burns.…”
Section: Resultsmentioning
confidence: 90%
“…The calculated sample size was calculated using one proportion formula. 9 Assuming a frequency of 47% 10 with two-sided confidence limits of 5%, 383 patients would be required, using 80% power level and 95% two-sided significance level. The sample size was increased to 400 participants to compensate for dropouts or protocol failures with incomplete data.…”
Section: Methodsmentioning
confidence: 99%